Impact of Actinobacillus pleuropneumoniae biofilm mode of growth on the lipid A structures and stimulation of immune cells. Issue 5 (July 2016) - Hathroubi, Skander; Beaudry, Francis; Provost, Chantale; Martelet, Léa; Segura, Mariela; Gagnon, Carl A; Jacques, Mario
Actinobacillus pleuropneumoniae (APP), the etiologic agent of porcine pleuropneumonia, forms biofilms on biotic and abiotic surfaces. APP biofilms confers resistance to antibiotics. To our knowledge, no studies have examined the role of APP biofilm in immune evasion and infection persistence. This study was undertaken to (i) investigate biofilm-associated LPS modifications occurring during the switch to biofilm mode of growth; and (ii) characterize pro-inflammatory cytokines expression in porcine pulmonary alveolar macrophages (PAMs) and proliferation in porcine PBMCs challenged with planktonic or biofilm APP cells. Extracted lipid A samples from biofilm and planktonic cultures were analyzed by HPLC high-resolution, accurate mass spectrometry. Biofilm cells displayed significant changes in lipid A profiles when compared with their planktonic counterparts. Furthermore, in vitro experiments were conducted to examine the inflammatory response of PAMs exposed to UV-inactivated APP grown in biofilm or in suspension. Relative mRNA expression of pro-inflammatory genes IL1, IL6, IL8 and MCP1 decreased in PAMs when exposed to biofilm cells compared to planktonic cells. Additionally, the biofilm state reduced PBMCs proliferation. Taken together, APP biofilm cells show a weaker ability to stimulate innate immune cells, which could be due, in part, to lipid A structure modifications.